2018
DOI: 10.24925/turjaf.v6i2.130-135.1408
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Reproductive Parameters Impairment of Cypermethrin in Male Guinea Pig (Cavia porcellus)

Abstract: Cypermethrin is a large spectrum action insecticide, globally employed to control pests in agriculture and some human and domestic animals ectoparasites. This study aimed to evaluate its toxicity and reproduction impairment in male guinea pig. Forty adult male guinea pigs were divided into 4 groups and orally submitted to 0, 92, 137.5 and 275 mg/kg body weight/day for 90 days. The weight of the liver increased significantly, while that of kidneys decreased significantly in treated animals compared to controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
6
3
0
Order By: Relevance
“…The histological structure of the kidney and liver were not considered in the present study to verify a possible alteration of function in these organs, and this can form basis for future investigation on this measure. However, increase in the serum level of urea (87.1%), creatinine (22.4%), ALAT (74.2%) and ASAT (88.7%) in the present study could be a consequence of functional and structural disturbance of the liver and kidneys as it has been reported elsewhere (Vemo et al., 2018). Abdel‐Wahhab et al.…”
Section: Discussionsupporting
confidence: 64%
“…The histological structure of the kidney and liver were not considered in the present study to verify a possible alteration of function in these organs, and this can form basis for future investigation on this measure. However, increase in the serum level of urea (87.1%), creatinine (22.4%), ALAT (74.2%) and ASAT (88.7%) in the present study could be a consequence of functional and structural disturbance of the liver and kidneys as it has been reported elsewhere (Vemo et al., 2018). Abdel‐Wahhab et al.…”
Section: Discussionsupporting
confidence: 64%
“…The testicular histopathology was damaged in Japanese quails exposed to AS, agreeing with findings of Ngoula et al (2017) in male Japanese quails exposed respectively to 37.5, 56.25 and 75 mg of AS/kg b.w for 49 days and Vemo et al (2018) in male guinea pigs exposed to 92, 137.5 and 275 mg/kg b.w/day of Cypermethrin for 90 days. The improvement in the testicular structure in animals treated with AEPAL observed in this study might be a consequence of AEPAL bioactive compounds' activity.…”
Section: Discussionsupporting
confidence: 87%
“…Several authors have reported on the protective effects of plant extracts against pesticides on secondary sexual characteristics and testis histology in mammal species (Wankeu et al, 2014, Vemo et al, 2018, but information related to birds remain rare.…”
Section: Introductionmentioning
confidence: 99%
“…Cypermethrin is also toxic to the reproductive system of male guinea pigs. In a study by Vemo et al (2018), four groups of adult male guinea pigs (10 animals each) were orally administered cypermethrin at doses of 0, 92, 137.5 and 275 mg/kg bw/day for 90 days. Before they were killed, at the end of exposure, the animal's libido (time of the male's reaction to the presence of a female) was studied.…”
Section: Discussionmentioning
confidence: 99%